2016
DOI: 10.1038/ejcn.2016.202
|View full text |Cite
|
Sign up to set email alerts
|

Screening for muscle loss in patients established on peritoneal dialysis using bioimpedance

Abstract: There is currently no agreed universal definition for sarcopenia, and prevalence varied markedly depending on the scoring system. Prevalence was not associated with small solute clearances, but was associated with sex, age co-morbidity, BMI and ethnicity. There was an association with dietary protein intake and urine volume, which may allow for dietary interventions and strategies to preserve urine output to reduce muscle loss in PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…We did not find any association between higher scores and loss of muscle mass. We measured muscle mass by bioimpedance, 32 and previous studies have reported differences using bioimpedance devices in HD patients, 7 , 33 and even though we allowed for reequilibration following the dialysis session, 34 further studies using DXA 35 or isotopic methods may be required to confirm our results.…”
Section: Discussionmentioning
confidence: 84%
“…We did not find any association between higher scores and loss of muscle mass. We measured muscle mass by bioimpedance, 32 and previous studies have reported differences using bioimpedance devices in HD patients, 7 , 33 and even though we allowed for reequilibration following the dialysis session, 34 further studies using DXA 35 or isotopic methods may be required to confirm our results.…”
Section: Discussionmentioning
confidence: 84%
“…The older, more comorbid demographic of the current dialysis cohort may differ from previously studied populations although UKRR data has consistently, somewhat paradoxically, shown higher sessional urea clearance amongst older patients [15][16][17]. Muscle mass declines with age [15], and dialysis patients with less muscle mass are less physically active [16] and have lower energy expenditure [17]. So, one may have expected higher dialyser urea clearances delivered to the younger rather than older patients [18].…”
Section: Discussionmentioning
confidence: 79%
“…A minimum dialysis adequacy appears to be necessary for patient wellbeing [1], but the benefits of higher clearance and the optimal dialysis dose have not been well defined [2][3][4][5]. The older, more comorbid demographic of the current dialysis cohort may differ from previously studied populations although UKRR data has consistently, somewhat paradoxically, shown higher sessional urea clearance amongst older patients [15][16][17]. Muscle mass declines with age [15], and dialysis patients with less muscle mass are less physically active [16] and have lower energy expenditure [17].…”
Section: Discussionmentioning
confidence: 83%
“…It was found that the sessional urea clearance delivered to older prevalent patients was greater than that for younger patients. Body composition changes with age as muscle mass declines [22], and as such both resting and total energy expenditure tend to decline with age along with dietary intake [10]. As such it would be expected that younger more active patients would require greater clearances than older patients.…”
Section: Discussionmentioning
confidence: 99%